Qualitative changes of different vegetable oils during repeated deep frying (Bangladesh Journal of Scientific and Industrial Research, 2022)
Repeated use of frying oils can produce elements that degrade food quality and promote the creation of chemicals with negative nutritional consequences and potential health risks. During multiple frying cycles in French fries, the quality of edible oils (soybean oil, rice bran oil, sunflower oil, and palm olein) was assessed. Except for RBO (F: 0.37-0.56 %), FFA percent was discovered in the usual range in SBO, SnFO, and PO. PV was raised by repeated frying, but SnFO showed the most instability (2.38-30.96) meq O2/kg. RBO produced the most trans-fat (0.85-1.21 percent), but SnFO did not produce any. While vitamin A content decreased after three frying cycles, the PO used before retained higher vitamin A (16.29-14.61 mg/kg). However, no oil, even extracted oils, holds up to the quality requirement after three frying cycles.Bangladesh J. Sci. Ind. Res. 57(1), 49-60, 2022